Another Look at Mutual Fund Tournaments - Busse, Jeffrey A. (Journal of Financial and Quantitative Analysis, 2001)
Daily returns are used to examine how mutual funds actively alter the risk of their portfolios in response to past performance. Compared to monthly data, daily returns produce much more efficient estimates of fund volatility, which give vastly different inferences about the behavior of fund managers. In particular, monthly results consistent with under-performers increasing their risk relative to better performing funds disappear with daily data. The differences in the monthly and daily results arise from biases in the monthly volatility estimates attributable to daily return autocorrelation.